2021
DOI: 10.1111/jcmm.16662
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylcholine antibodies restrict infarct size and left ventricular remodelling by attenuating the unreperfused post‐ischaemic inflammatory response

Abstract: Phosphorylcholine is a pro‐inflammatory epitope exposed on apoptotic cells, and phosphorylcholine monoclonal immunoglobulin (Ig)G antibodies (PC‐mAb) have anti‐inflammatory properties. In this study, we hypothesize that PC‐mAb treatment reduces adverse cardiac remodelling and infarct size (IS) following unreperfused transmural myocardial infarction (MI). Unreperfused MI was induced by permanent ligation of the left anterior descending (LAD) coronary artery in hypercholesterolaemic APOE*3‐Leiden mice. Three wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…AMI can lead to cardiomyocyte death, often followed by a robust inflammatory response in myocardial tissue. Previous studies have demonstrated that the activation of complement and Toll-like receptor (TLR)/interleukin-1 (IL-1) signaling is involved in the onset and development of inflammation [12][13][14]. A suitable inflammatory response is beneficial for the healing of injured myocardial tissue, indicating that the body performs the function of self-repair.…”
Section: Introductionmentioning
confidence: 99%
“…AMI can lead to cardiomyocyte death, often followed by a robust inflammatory response in myocardial tissue. Previous studies have demonstrated that the activation of complement and Toll-like receptor (TLR)/interleukin-1 (IL-1) signaling is involved in the onset and development of inflammation [12][13][14]. A suitable inflammatory response is beneficial for the healing of injured myocardial tissue, indicating that the body performs the function of self-repair.…”
Section: Introductionmentioning
confidence: 99%
“…The IgG PC-mAb is also able to block oxLDL uptake by macrophages unlike the T15/E06 based IgG and binds late apoptotic cells, but not normal or ‘early’ apoptotic cells [ 3 ]. We recently showed that PC-mAb prevented macrophage influx after myocardial infarction via reduced systemic inflammatory responses [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%